Thermodynamic modeling and exergy optimization of a gas turbine power plant - Mohd. Jaafar, Mohammad Nazri (IEEE, 2011)
Due to the importance of increasing power plants performance in Iran Exergy analysis is a common way for these cycles, Thus For this analysis first each part of gas Turbine Plant were modeled by thermodynamic approach then The effect of changing in the inlet turbine temperature on the exergy efficiency and exergy destruction in this plant was evaluated. The results show that the exergy efficiency of the combustion chamber is much lower than that of other plant components due to chemical reaction and the large temperature difference between the burners and working fluid. In addition, these calculations are performed for 50 and 75% G.T base load and results show that the exergy destruction when G.T work in base load is more than full load. More ever the optimizations process has been follow in this paper, therefore in this regard the economic objective function has been defined and minimized.